"I Can Relate": Survivor Leadership Supporting Women Transitioning Out of the Sex Trade. Issue 4 (November 2019) - Deer, Shannon; Baumgartner, Lisa
In this article, the authors examine the value of survivor leaders in organizations helping women transition out of the sex trade and how organizations can best utilize survivor leaders. They interviewed 10 women who have been out of the sex trade from between 3 and 20 years. They found survivor leaders (a) created relatability for participants exiting out of the sex trade, (b) modeled a hopeful future, and (c) mitigated power issues. The authors uncovered three ways organizations can engage survivor leaders: (a) on boards, (b) in paid staff positions, and (c) as volunteers. They discuss the ethical and financial issues associated with organizations using unpaid and paid survivor leaders. Furthermore, the authors recommend practical ways organizations can improve by engaging survivor leaders in peer education, policy setting, and management. They also encourage organizations to view survivors as experts. The authors' findings move adult education beyond a focus on peer education to considering peer leadership.